ISOLASI dan IDENTIFIKASI SALMONELLA SP PADA DAGING AYAM SEGAR YANG DIJUAL DI PASAR LEGI PONOROGO - Susilowati Andari; Devita Yudhayanti (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
Chicken is one of the source of protein that is widely consumed by the public because it contains nutrients at affordable prices and easy to obtain. Various processed foods from chicken are widely developed in the community. Safe food is one that is free from contamination, both physical, chemical, and microbiological. Microbiological food safety is major concern in the world of health because it causes various disease problems. The most frequently reported disease due to this bacterial infection is typhoid. Based on SNI 7388 2009 concerning the maximum limit of microbial contamination in food, it is stated that fresh chicken meat must not contain the pathogenic bacteria Salmonell sp. To protect the public from these danger and increase awareness about food safety, it is necessary to conduct research on the presence of Salmonella sp microbial contamination in fresh chicken meat, especially those sold in the research area, namely Ponorogo. The problem can be formulated to wheter there si the contamination of Salmonella sp bacteria in fresh chicken meat sold at Legi Market Ponorogo. The purpose of this study was to isolate and identify Salmonella sp in fresh chicken meat sold at Legi Market Ponorogo. The long-term goal of this research is to increase public awareness of microbiological hazards in food, especially chicken meat. Sampling was conducted randomly on traders at Legi Market Ponorogo. Of the ten samples analyzed, eight samples were isolated and identified the presence of Salmonella sp. This illustrates that there are still a lot of fresh chicken meat sold in Legi Market Ponorogo that does not meet the quality based on SNI 7388 2009, which is 80 %.